Agriculture of Akmola region: state and prospects - Kurmanova Д.; Ukibaуeva Г.; Nurtazinova А. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2022)
The article analyzes the main indicators of the development of agriculture in Akmola region for 2014-2020, such as: gross agricultural output, gross crop and livestock production, structure of gross output and sown areas, production of certain types of livestock products and livestock productivity. In 2021, the implementation of the State program of the agro-industrial complex of the Republic of Kazakhstan for 2017-2021 is coming to the end and there is made an attempt to assess the activities of the industry. Based on the analysis, it was revealed that a lot of projects have been done and implemented in the industry, which have given positive results. But there are still a number of unresolved issues and problems that need to be addressed. The development of agriculture can lead to sustainable economic development and, accordingly, to state security.